IC and Firms Performance: The Moderating Effect of Malaysia Corporate Government Code 2012 and 2017 - Saleh, Haider Mahdi; Abdul Rahman, Mara Ridhuan Che; Hasan, Mohamat Sabri; Ahmad, Azlina (International Journal of Psychosocial Rehabilitation, 2020)
In the age of knowledge economy Intellectual Capital (IC) is gaining prominence in academic research and management practices owing to the fact that it is a significant contributor to strong performance creation. To achieve maximum performance, corporate governance (CG) mechanism plays an important role by enhancing the management of IC practice via effective control, measurement, and reliable reporting of IC. In 2017, Malaysia witnessed the reform of corporate governance emphasizing a holistic structural change. Arguably, such reforms could result in better IC management practice compared to the prior CG code established in 2012. However, the desired effect of the new code on IC with respect to strong performance has not been tested thus far. This study, therefore, was carried out with the aim to compare the effect of IC on strong performance between pre- and post-Malaysian Code of Corporate Governance 2017 practices. The study involved three research objectives, which were to investigate the associations of IC and performance, to compare the moderating effects of MCCG 2012 and MCCG 2017 practices on such associations relating to the desired improvement between the codes, and to compare the moderating effects of mandatory CG 2012 and 2017 practices CG practices on such associations. The research data consisted of information derived from the financial years of 2015, 2016, 2017, and 2018. The CG index of mandatory practice was developed using MCCG 2012 and 2017 codes. Value Added Intellectual Coefficient (VAIC) was calculated to measure IC performance. The findings showed that the total VAIC was associated with performance. Furthermore, the sub-analysis of VAIC revealed that only human capital efficiency was significantly associated with performance and human capital and structural capital efficiencies were not significantly associated with firm performance. Regression results indicated that mandatory CG practices significantly moderated the relationships between VAIC and firm performance. The findings also showed that the moderating effect of MCCG 2017 was stronger than that of MCCG 2012, indicating that regulators’ efforts in reforming CG practice code had achieved their aims. Based on such findings, an investment in human capital is paramount to improving performance. In addition, such findings provide empirical support for resource base view and agency theory where a better corporate governance mechanism can contribute to the significant association between IC management practices and firm performance.